Observation of electron-transfer-mediated decay in aqueous solution - Unger, Isaak; Cederbaum, Lorenz S.; Kryzhevoi, Nikolai V. (Nature chemistry, 2017)
Photoionization is at the heart of X-ray photoelectron spectroscopy (XPS), which gives access to important information on a sample's local chemical environment. Local and non-local electronic decay after photoionization—in which the refilling of core holes results in electron emission from either the initially ionized species or a neighbour, respectively—have been well studied. However, electron-transfer-mediated decay (ETMD), which involves the refilling of a core hole by an electron from a neighbouring species, has not yet been observed in condensed phase. Here we report the experimental observation of ETMD in an aqueous LiCl solution by detecting characteristic secondary low-energy electrons using liquid-microjet soft XPS. Experimental results are interpreted using molecular dynamics and high-level ab initio calculations. We show that both solvent molecules and counterions participate in the ETMD processes, and different ion associations have distinctive spectral fingerprints. Furthermore, ETMD spectra are sensitive to coordination numbers, ion-solvent distances and solvent arrangement.